Niobium/Vanadium doped TiO2 multilayered sol-gel films: Structure, surface chemistry and optical properties. Issue 12 (September 2016) - Covei, Maria; Predoana, Luminita; Osiceanu, Petre; Calderon-Moreno, Jose Maria; Anastasescu, Mihai; Preda, Silviu; Nicolescu, Madalina; Gartner, Mariuca; Zaharescu, Maria
Abstract: In this work multilayered TiO2 films deposited on glass and Si substrates by the sol-gel – dipping method were studied, focusing on the influence of Niobium/Vanadium doping on the structure, surface chemistry and their optical properties. The TiO2 films doped with 1.2 at% Nb(V) crystallized in anatase phase as evidenced by XRD analysis. It was found that thicker films are obtained in the case of V-doped TiO2 films, while the values of the optical band-gap show similar values. Bands related to the vibration of oxygen in the Ti–O, Nb–O and V–O bonds were identified based on Infrared Spectroscopic Ellipsometry, proving the incorporation of the dopants in the matrix of the TiO2 films. Both types of doped films exhibit around 80% transparency on a wide spectral range (300–1700 nm). Niobium and Vanadium have been identified in the surface / subsurface region in the 5+ oxidation state (although a high sensitivity of the Vanadium oxidation states during profiling experiments was found due to the preferential sputtering effect). From a morphological point of view, all titania films show a very uniform and compact microstructure, with a homogeneous superficial structure of small grains with diameters in the range of 10–20 nm.